The perceptions of pharmacists in Victoria, Australia on pharmacogenetics and its implications - McMahon T; Tucci J (Centro de Investigaciones y Publicaciones Farmaceuticas, 2011)
Objectives: This study aimed to explore how well Victorian pharmacists perceived they understood pharmacogenetics, their perceived capacity to counsel a patient about such testing, how they believed pharmacogenetics would impact upon their profession, and to investigate the ways in which Victorian pharmacists would like to be educated about pharmacogenetics.Methods: A cross-sectional survey was dispatched to 800 Victorian pharmacists. The participants were randomly selected and the survey was anonymous. The survey contained questions about where the pharmacists worked, the pharmacists' perceived knowledge of pharmacogenetics, how well they believed they would be able to counsel patients about pharmacogenetic testing, how they thought pharmacists should be educated on the topic and how they believed pharmacogenetics would impact upon their profession.Results: 291 surveys were returned (36% response rate). Results suggest that Victorian pharmacists generally perceived they had a poor understanding of pharmacogenetics and that those who have more recently graduated from tertiary education had a better perceived understanding than those who have been in the workforce for longer. Most pharmacists indicated that they did not believe that they could counsel a patient adequately about the results of a pharmacogenetic test. Regarding education about pharmacogenetics, participants suggested that this would be best delivered during tertiary studies, and as seminars and workshops forming part of their continuing professional development. Although some pharmacists were unsure how pharmacogenetics would affect their profession, many believed it would have a major impact upon their role as a pharmacist and lead to improved patient care. Some concerns about the implementation of pharmacogenetics were noted, including economic and ethical issues.Conclusion: This study highlights the need for further research across the pharmacy profession in Australia on the issue of preparedness for the putative incorporation of pharmacogenetics into the healthcare system and everyday practice.